Population aging, the composition of government spending, and endogenous economic growth in politico-economic equilibrium - Kuehnel, Johanna (Discussion paper series, 2011)
This paper introduces a democratic voting process into an OLG economy in order to analyze the e ffects of a rising old-age dependency ratio on the composition of government spending and endogenous economic growth. Forward-looking agents vote each period on the public policy mix between productive government expenditure and public consumption spending that benefi ts the elderly. Population aging shifts political power from the young to the old. While this does not aff ect public productive expenditure, it leads to an increase in public spending on the elderly and a slowdown in economic growth. However, the overall e ffect on long-term economic growth is positive. This is due to reduced capital dilution or increased saving.